Epitaxial PtMn/NiFe exchange-biased bilayers containing directly deposited ordered PtMn - Choi, Y; Petford-Long, A; Ward, R (2005)
PtMnNiFe exchange-biased bilayers have been grown epitaxially on Si (001) using molecular-beam epitaxy. Spontaneous formation of the chemically ordered face-centered-tetragonal phase of PtMn layer was confirmed without postgrowth magnetic-field annealing, whose Ńel axis is perpendicular to the PtMnNiFe interface. The exchange anisotropy field stabilizes above a PtMn thickness of 15 nm which is much lower than that for polycrystalline PtMn-based exchange-biased systems. For comparison, PtMnNiFe exchange-biased bilayers have been prepared epitaxially on MgO (001) substrate. Spontaneous formation of the chemically ordered PtMn layer was also confirmed with Ńel axis parallel to the PtMnNiFe interface. The exchange anisotropy field of the bilayer on MgO stabilizes beyond a PtMn thickness of 15 nm as well. © 2005 American Institute of Physics.